2020
DOI: 10.3892/ol.2020.11945
|View full text |Cite
|
Sign up to set email alerts
|

Markers of epithelial-mesenchymal transition in an experimental breast cancer model induced by organophosphorous pesticides and estrogen (Review)

Abstract: Breast cancer is a major health problem and accounted for 11.6% of all new cancer cases and 6.6% of all cancer deaths among women worldwide in 2018. However, its etiology has remained elusive. According to epidemiological studies, environmental factors are influencing the increase in the incidence of breast cancer risk. Components such as chemicals, including pesticides, are agents that produce deleterious effects on wildlife and humans. Among them, the organophosphorus pesticides, such as malathion, have larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Further, the TGF-β pathway has been pharmacologically targeted using a multitude of approaches including small molecule inhibitors, TGF-β-directed chimeric monoclonal antibodies, ligand traps, and vaccines [144]. Organophosphorus pesticide exposure enhanced the protein expression of EMT associated proteins vimentin, ax1, and slug [145], while chlorpyrifos (CPF), one of the most frequently used pesticides around the world, increased MMP2 and vimentin expression driving breast cancer invasion [90].…”
Section: Role Of Pesticides In Emt and Metastasismentioning
confidence: 99%
“…Further, the TGF-β pathway has been pharmacologically targeted using a multitude of approaches including small molecule inhibitors, TGF-β-directed chimeric monoclonal antibodies, ligand traps, and vaccines [144]. Organophosphorus pesticide exposure enhanced the protein expression of EMT associated proteins vimentin, ax1, and slug [145], while chlorpyrifos (CPF), one of the most frequently used pesticides around the world, increased MMP2 and vimentin expression driving breast cancer invasion [90].…”
Section: Role Of Pesticides In Emt and Metastasismentioning
confidence: 99%
“…The authors proposed that EBV presence affects the response of BC cells to nicotine [ 103 ]. In addition, it has been shown that organophosphate pesticides such as malathion or parathion are related to BC by in vitro and in vivo approaches [ 104 , 105 , 106 ]. Notably, it was reported that chlorpyrifos, an organophosphate pesticide, can promote EBV lytic cycle activation by promoting BZLF1 expression by oxidative stress in a lymphoblastoid cell line.…”
Section: Ebv In Breast Cancer: Potential Mechanismsmentioning
confidence: 99%
“…On the other hand, the influence of ERα-signaling pathways on epithelial-to-mesenchymal transition-related transcriptional factors, which are fundamental in the development of breast cancer, has been reported ( 34 , 35 , 101 , 102 ).…”
Section: Parathion and Malathion Modulate Epidermal Growth Factor Recmentioning
confidence: 99%